THE EFFECT OF INSTITUTIONAL OWNERSHIP, PROFITABILITY, COMPANY GROWTH, AND DEBT RATIO ON DIVIDEND POLICY (Study on Banking Companies Listed on the Indonesia Stock Exchange Period 2015-2017) (Ekspektra : Jurnal Bisnis dan Manajemen, 2022)
This study aims to determine which a factor is the most dominant in influencing a dividend policy in banking companies listed on the Indonesia Stock Exchange for the period 2015-2017. The method in this study uses a quantitative associative type. The sampling technique used in this study was the purposive sampling with the sample required for this study, namely 27 companies. the analysis of the data used in this study is the classical assumption test, a multiple regression analysis and a hypothesis testing. The results showed that the t value of Institutional Ownership (KI) was 1.1760.05 means no effect, the t value of a profitability (ROA) is 2.071> from the t table 1.99125 with a sig. 0.033 <0.05 means that it has a positive effect, the t value of Company Growth (GRWT) is -2.685> from the t table 1.99125 with a sig. 0.046 <0.05 means that it is influential, the t value of the debt ratio (DER) is -2.031> from the t table 1.99125 with a sig. 0.041 <0.05 means that it has a negative effect on a dividend policy. These results also indicate that the variable that has a dominant effect, namely the variable profitability measured using ROA, has a positive and significant effect on the variable dividend policy (DPR).